Case Report: Shadows of disappearance: the enigma of completely regressed cutaneous melanoma revealed by lymph node metastasis - Wang, Li; Li, Yingxue; Zhang, Xinyan; Han, Lin; Xia, Zhangyong (Frontiers in Oncology, 2025)
Primary cutaneous malignant melanoma is an aggressive neoplasm with high metastatic potential. Complete spontaneous regression of the primary lesion is rare, poorly understood, and often leads to diagnostic challenges, particularly when the cutaneous origin is no longer clinically or histologically evident. We report two cases of completely regressed cutaneous melanoma that initially presented as unexplained lymphadenopathy and were diagnosed through fine needle aspiration cytology (FNAC) and pathological examination. Both patients were admitted to non-dermatological departments due to regional lymphadenopathy. FNAC of the lymph nodes revealed malignant cells with features suggestive of melanoma. In both cases, immunocytochemical staining of cell block preparations confirmed melanocytic origin, with positivity for SOX10, HMB45, and Melan-A, and negativity for markers excluding hematolymphoid and epithelial neoplasms. Notably, neither patient had a prior history of malignancy. One patient had been misdiagnosed with onychomycosis for two years, reevaluation revealed a regressed subungual lesion while the other patient described a longstanding black lesion on the fifth fingertip that spontaneously resolved without nail involvement. These cases highlight the crucial role of cytology and immunohistochemistry in the diagnosis of metastatic melanoma when the primary lesion has fully regressed. They underscore the need for a high index of suspicion, comprehensive clinical history, and close collaboration between clinicians, cytopathologists, and dermatologists. Greater awareness of this rare presentation is essential to prevent misdiagnosis and ensure timely and accurate treatment.